Role of the Turkish media in forming the orientations of Turkish public opinion toward the attempted coup of 15 July 2016 - A. Aldebaisi, Abdulkareem; F. Khasawneh, Ibrahim; A. Özdemir, Mehmet (ALBAHITH ALALAMI, 2021)
The present study aims to illuminate the assessment of the Turkish elite of the role of the Turkish media in forming the attitudes of public opinion vis a vis the attempted military coup of 15 July 2016. The authors utilized the survey method of a nominal sample of 315 individuals, equally distributed among the three foremost categories of the Turkish elite, namely: the political academic, and media elite. The foremost findings of the study are that the orientation of the coverage of the Turkish media of the events of the attempt military coup of 15 July, based on the perception and assessment of the Turkish elite, was positive to a high degree; it refuted the news and the inciting information given to foreign media revealed the bloodiness of the rebels who opened fire on innocent civilians, and adopted a media discourse supportive of the national will and the safeguarding of democracy. The Turkish media also urged Turkish political parties to adopt a united stand toward the coup, in a manner different from its positions toward the military coups that took place previously in Turkey. Moreover, it is the view of the elite that the Turkish media contributed to forming the attitudes of Turkish public opinion that are strongly opposed to the annulment of democracy. This helped abort the coup attempt, and this evidenced and proved the strong influence of the Turkish media on society.